Correlation between the characteristic green emissions and specific defects of ZnO - Liang, Meng Heng (2011)
In this work, the correlation between the characteristic green emissions and specific defects of ZnO was investigated through a series of experiments that were designed to separate the subtle interplays among the various types of specific defects. With physical analysis and multimode Brownian oscillator modeling, the underlying mechanisms of the variant effects on green emission were revealed. The results demonstrate that the observed green emissions can be identified as two types of individual emissions, namely high energy and low energy, that are associated with specific defects and their locations. The surface modification that leads to downwards band bending was found to be responsible for the high-energy green emission. The relationship between the intensity of the low- energy green emission and the crystallographic lattice contraction indicates that oxygen vacancy is the dominant cause of such an emission that resides within the bulk of ZnO.